Self-efficacy, mental models and team adaptation: A first approach on football and futsal refereeing - Aragão e Pina, J.; Passos, A. M.; Maynard, M. T.; Sinval, J. (Psychology of Sport and Exercise, 2021)
Objective: Within the football and futsal refereeing context, even though referees work within teams, there is very little research considering the implications of team dynamics. In response, this study starts to address this gap in the literature by investigating the moderating effect of mental models on the relationship between self-efficacy beliefs and perceptions of team adaptation within the exciting context of professional and national football and futsal refereeing. Design: We obtained online questionnaires from 339 active football and futsal referees within the National and Professional league at two distinct points (April and May) within the football season. Results: Self-efficacy beliefs were positively associated with perceptions of team adaptation (only for football referees). Mental models were positively associated with team adaptation. Likewise, the moderation between mental models and self-efficacy beliefs was positively associated with perceptions of team adaptation (only for futsal referees). However, such an effect was only significant at the futsal referees’ level. Conclusion: This study emphasises the importance of mental models for team adaptation and the importance of self-efficacy beliefs in predicting perceptions of team adaptation. We hope that this study represents the first step in a greater appreciation of the salience of team dynamics and their impact on football and futsal referees’ performance and that future research can build upon our work.